STUDY OF THE EFFECT OF THE FILTRATION ON THE FILM BADGE SENSITIVITY BY USING THE ROENTGEN TUBE TYPE PANTAK HF-320 - Al-Mashhadani, Nahida J H (Al-Nahrain Journal of Science, 2009)
This work is carried out at The NOFER Institute laboratories of Occupational Medicine, Lodz Poland. The aim of this research is to study of the filtration effect on the personal film badge XO film type (Foton –Warszawa, Poland) sensitivity by using the roentgen tube type Pantak HF-320 and the water slab phantom as recommended by NCRP. By changing the radiation energy at fixed dose, the film sensitivity will change according to the mean energy. It is found that the maximum sensitivity for the film approaches the energy of 33 keV. Construction of a film holder (badge), which contains the filters, four pairs of filters (0.05 mm Cu, 0. 5 mm Cu, 1. 5 mm Cu and 1.0 mm Pb), moreover, there is an open window in the badge. The holder filters will overcome the sensitivity changing of the film, so it must be used. It is found that, there is decreasing in optical density according to the increasing of Cu-filter thickness, the optical density of the Pb is the lowest in the (24-248keV) range. There is increasing in optical density (film sensitivity) by changing the radiation energy at fixed dose up to 33keV, which record the maximum sensitivity of the film. Anon–linear correlation has been found between the optical density and the radiation dose, this curve, called–calibration curve. The typical background of the film has been found below 0.1 mSv, thus the lowest measurable dose was calculated to be 0.1 mSv. It is found that the optical density increases with the absorbed dose, which is attributed to the photo degradation of the films, may induce localized states in the energy gap causing increasing in optical absorption up to (33keV). For the high energy, the optical density decreases, which attributed to the photo degradation of the films may cause some cracks at the film surface. The optical analysis of the film surface in the sites shielded by the filters and in the open window allows calculating three components of the radiation spectrum of energy weak, medium and hard. The method described by Dresler method is to determine calibration function. This method in film badge calibration is more accurate than that used which uses gamma source (Ra-226) as a calibration source in our country, because of using x-ray source of different energy is taking into account the exposing radiation of different energy of the worker in radiation field, its effect on the film sensitivity, and the personal dosimeter.